2023
DOI: 10.1371/journal.pone.0281627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preschool attendance, parental stress, and parental mental health on internalizing and externalizing problems during COVID-19 lockdown measures in preschool children

Abstract: Background Internalizing problems are common in young children, often persist into adulthood, and increase the likelihood for subsequent psychiatric disorders. Problematic attachment, parental mental health problems, and stress are risk factors for the development of internalizing problems. COVID-19 lockdown measures have resulted in additional parental burden and especially their impact on preschool children has rarely been investigated as of now. The current study examined the impact of sustained preschool a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 90 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…Parental mental health symptoms at the beginning of the pandemic had direct effects on higher levels of child problem behaviors. This supports previous literature that found maternal depressive symptoms (Gordon-Hacker et al, 2023) and maternal anxiety symptoms (Jarvers et al, 2023) are linked to later emotional and behavioral problems in children. Parents struggling with more pandemic-related stressors likely face increased mental health symptoms, and thus find sensitive and responsive parenting more challenging.…”
Section: Parental Mental Health and Child Problem Behaviorssupporting
confidence: 91%
“…Parental mental health symptoms at the beginning of the pandemic had direct effects on higher levels of child problem behaviors. This supports previous literature that found maternal depressive symptoms (Gordon-Hacker et al, 2023) and maternal anxiety symptoms (Jarvers et al, 2023) are linked to later emotional and behavioral problems in children. Parents struggling with more pandemic-related stressors likely face increased mental health symptoms, and thus find sensitive and responsive parenting more challenging.…”
Section: Parental Mental Health and Child Problem Behaviorssupporting
confidence: 91%
“…In the 6-18-year-old subgroup, anxiety (n = 74, 28%), depression (n = 51, 19%), somatic problems (n = 43, 16%), attention problems (n = 20, 8%), oppositional problems (n = 16, 6 %), and conducted (n = 6, 2%) were the most prevalent disorders [44]. In the research by Jarvers et al, internalizing and externalizing problems significantly increased with time in preschoolers, peaking during the lockdown and only slightly declining after the lockdown [45]. Schmidt et al found that, among 5823 children, from 2.2% to 9.9% reported emotional and behavioral issues that were beyond the clinical cut-off.…”
Section: Discussionmentioning
confidence: 91%
“…Since the comparison between Time 0 and Time 1 was analyzed in one of our previous studies [33], we present here the results of the comparison between Time 1 and Time 2 in order to monitor symptoms after one year of the pandemic. While there are many studies comparing the mental health status of Italian neuropsychiatric patients before and during the first lockdown [3,19,22,30,39], to the best of our knowledge, our study is the first that has attempted to assess the long-term effects of the COVID-19 lockdown on mental health. Our sample included 369 patients and their families (Tables 1 and 2), aged between 2-18 years, with the following neuropsychiatric diagnoses: autism spectrum disorder (n = 110), epilepsy (n = 90), specific learning disorders (n = 40), intellectual disability (n = 33), communication disorders (n = 29), attention deficit/hyperactivity disorder (n = 21), behavioral disorders (n = 16), anxiety disorders (n = 15), and mood disorders (n = 15).…”
Section: Discussionmentioning
confidence: 99%